The Cantabrian Fault at Sea. Low Magnitude Seismicity and Its Significance Within a Stable Setting - Fernández-Viejo, Gabriela; Llana-Fúnez, Sergio; Acevedo, Jorge; López-Fernández, Carlos (Frontiers in Earth Science, 2021)
The Cantabrian fault (CF) is a crustal-scale structure that cuts obliquely the western North Iberian Margin (NIM) for 160 km and continues onshore transecting the Cantabrian Mountains (CM) as the Ventaniella fault (VF).Inland, the fault is aseismic, except for a 70 km segment at its southern end. Here, a gently north-dipping arrangement of earthquakes was interpreted as related to the intersection of a slightly oblique fault to VF with the basal thrust of the CM. In addition to earthquake nucleation, the CF-VF also stands out regionally as a major seismotectonic boundary, separating a seismically active western area from an essentially aseismic eastern one. Contrasting tectonothermal crustal evolution on either side during the Mesozoic rifting may underlie the observed differences. On the other hand, the seismicity within the subsea segment is low magnitude, persistent, and understudied. The scarcity of permanent seismic stations in the area did not allow but to stablish a generalized consensus relating the offshore events to the CF. A local seismic network monitored the area providing the highest accuracy on the offshore events to date. Although foci location is partially challenged by the lack of recording stations from northern azimuths, the observed pattern shows indeed a broad linear trend following the crustal fault. This study shows that the distribution of offshore foci displays two preferential areas along the CF-VF within its southern crustal block. Considering the basement rock types and the architecture of the margin, two possible explanations for the clusters origin are put forward in this contribution.